New types of African heroines in Hollywood: Black Panther - Yasantha Devi Chandiran; Shanthini Pillai Joseph Sandra (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2020)
The release of the much anticipated movie Black Panther in February of 2018, saw the splendour of a predominantly Black cast while the movie also highlighted the strength and empowerment of Black women. The historic notion is that Black women were conditioned to be obedient and submissive but Black Panther contrasts the archaic stereotypes of Black women by introducing women with qualities of the complete opposite. This superhero movie challenges the traditional notion of existing social rules that African women are expected to follow. This indicates a thriving but modest focus on the transformation and changes of social structure among Black women. Thus, this paper draws from an academic exercise that explores the characters of Black women portrayed in Black Panther and how it transforms the traditional Black female roles in Hollywood films.